Application of Snowball Throwing Method in Islamic Religious Education Subject at TMI Roudlatul Qur'an Metro Middle School Lampung - Cindy Antasya; Irhamudin Irhamudin; M. Sayyidul Abrori (Journal of Research in Islamic Education, 2025)
This study aims to analyze how the application of the Snowball Throwing learning method in Islamic religious education subjects in the classroom. The identification of the problem of this study is that learning is still centered on educators, educators have not been optimal in choosing the right learning method during the learning process. This study uses a qualitative descriptive method with data collection techniques through interviews, observations and documentation. Data analysis uses data collection, data condensation, data presentation, and drawing conclusions. To test the validity of the data, researchers use triangulation techniques and source triangulation. Based on the results of the analysis of researchers in this problem, the results of the study show that the application of the snowball throwing learning method in Islamic religious education subjects which in its application uses rolled paper can increase students' interest and understanding in learning, because this snowball throwing learning method creates a pleasant and not boring atmosphere. The implementation of the snowball throwing learning method includes 3 stages, namely, planning, implementation and assessment. Teacher planning such as preparing good lesson plans and materials to maximize when explaining the material to students in class. Implementation, students are formed into several groups of 5-6 people and write questions on blank paper then thrown to other students. Evaluation, namely enrichment and daily values.